IMPLEMENTASI MODEL PEMBELAJARAN KONTEKSTUAL DALAM MENINGKATKAN HASIL BELAJAR KEWIRAUSAHAAN DITINJAU DARI MINAT OUTDOOR MAHASISWA PRODI PENDIDIKAN EKONOMI STKIP HAMZANWADI - zein, rohaeniah (Universitas Hamzanwadi, 2012)
This research aimed to find out the effect of contextual learning model on natural science learning achievement viewed from outdoor interest of 112 grade students of cluster II grade Economic Education of Stkip Hamzanwadi students of Selong East Lombok. The sample was 76 students taken randomly using random sampling. The research method was experimental research, of the posttest only control group design. The data were gathered using questionnaire for outdoor interest and multiple-choice test for natural science learning achievement. The data were analyzed using two-way Anova. The result of the research shows that: (1) there is a difference of natural science learning achievement between students following contextual learning model and those following conventional learning model (FA = 67,90; p<0.05), (2) there is an interactional effect between contextual learning model and natural science learning achievement (FAB = 27.49; p<0.05), (3) for students having high outdoor interest, there is a difference of natural science learning achievement between students following contextual learning model and those following conventional learning model (Q = 15.91; p<0.05), (4) for students having low outdoor interest, there is a difference of natural science learning achievement between students following contextual learning model and those following conventional learning model (Q = 6.79; p<0.05). Keywords: Contextual Learning Model, Natural Science Learning Achievement, Outdoor Interest